General anesthesia combined with thoracic epidural anesthesia: an anesthesia technique option in modified radical mastectomy - Sidemen, I Gusti Ayu Eka Para Santi; Senapathi, Tjokorda Gde Agung; Widnyana, I Made Gede; Aribawa, I Gusti Ngurah Mahaalit; Ryalino, Christopher (Bali Journal of Anesthesiology, 2019)
The incidence of breast cancer has been increasing, and currently, it is the most common cancer in females. Surgery is the primary treatment, and the current tendency is toward less extensive procedure with axillary dissection for removal of lymph nodes to guide further treatment, in this case, the method called modified radical mastectomy (MRM).  The anesthetic technique for MRM should provide adequate intraoperative anesthesia, muscle relaxation, and postoperative analgesia without collateral effects, nausea, and vomiting with the minimum hospitalization time. In this report, we present a case of a woman who underwent MRM under general anesthesia combined with thoracic epidural anesthesia.